Meso scale component manufacturing: a comparative analysis of non-lithography and lithography-based processes. (1st June 2022) - Khalid, Azfar; Wei, Yang; Saleem, Muhammad Rizwan; Lughmani, Waqas Akbar
Abstract: The paper identifies the meso scale (10 µ m to few millimeters) component size that can be manufactured by using both lithography and non-lithography based approaches. Non-lithography based meso/micro manufacturing is gaining popularity to make micro 3D artifacts with various engineering materials. Being in the nascent stage, this technology looks promising for future micro manufacturing trends. Currently, lithography based micro manufacturing techniques are mature, and used for mass production of 2D, 2.5D features and products extending to 3D micro parts in some cases. In this paper, both the techniques at state-of-the-art level for meso/micro scale are explained first. The comparison is arranged based on examples and a criterion is set in terms of achievable accuracy, production rate, cost, size and form of artifacts and materials used. The analysis revealed a third combined approach where a mix of both techniques can work together for meso scale products. Critical issues affecting both the manufacturing approaches, to advance in terms of accuracy, process physics, materials, machines and product design are discussed. Process effectiveness guideline with respect to the component scale, materials, achievable tolerances, production rates and application is emerged, as a result of this exercise.